Influence of veining on tensile strength and fragmentation of brittle rock in cave mining - Noori, S; Harraden, C; Eberhardt, E; Iferobia, C (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
As mining operations target greater depths, the mechanical behaviour of rock masses becomes increasingly complex due to the combined effects of high in situ stresses and the growing dominance of vein networks in low joint intensity rock masses, such as those associated with porphyry deposits. This complexity underscores the importance of orebody knowledge, as the mineralogical and structural characteristics of veining can exert a first-order control on rock mass behaviour and fragmentation processes. While the role of faults and joints has been extensively studied, the influence of veining on rock strength, brittle fracture and fragmentation remains poorly understood. This study examines the impact of vein mineralogy and morphology on the tensile strength and fracture propagation of diorite and skarn using Brazilian tensile strength testing. Veined specimens were tested under controlled laboratory conditions, with fracture propagation monitored using a high-resolution video imaging technique. Fracture responses were classified as crossing, deflecting along the vein–host rock interface or localising along the vein. Vein attributes, including mineralogy and morphology, were shown to exert a strong control on fracture behaviour and tensile strength. In particular, the mechanical contrast between the vein and the host rock played a critical role in fracture development when the dominant vein was oriented at approximately 30° relative to the loading direction. Weak veins preferentially localised fracture propagation, whereas veins with mechanical strength comparable to the host rock were typically crossed by propagating fractures. In contrast, veins that were stronger than the host rock promoted crack deflection or arrest, forcing fractures to propagate through the host rock or along vein–host rock interfaces. Vein and host rock mineralogy are characterised using micro-X-ray fluorescence imaging, shortwave infrared spectroscopy and thin-section petrography. By quantifying how vein properties influence fragmentation behaviour, this research advances understanding of veined rock behaviour and provides insights for geomechanical assessments in deep cave mining environments.
Keywords: orebody knowledge; veined rock; vein mineralogy; vein geometry; Brazilian tensile strength; brittle fracture behaviour; deep cave mining geomechanics